Multisensory Experience Design in Semarang's Culinary Destinations: Its Impact on Memorable Tourism Experience and Revisit Intention - Heri Usodo; Heru Yulianto; Muhammad Julianto; Firda Sekar Praditya (Pusat Riset dan Inovasi Nasional, 2026)
Culinary tourism has emerged as a vital segment of the tourism industry; however, tourist interest in Central Java's culinary sector remains relatively low (13.02%). This study investigates the implementation of multisensory experience design in Semarang's culinary destinations, explores its contribution to the formation of Memorable Tourism Experience (MTE), and examines its influence on revisit intention. Employing a qualitative phenomenological approach, the research engaged 30 informants through in-depth interviews, participatory observations, sensory mapping, and focus group discussions conducted at five key culinary sites. Thematic analysis revealed five dimensions of multisensory experience, with olfactory and gustatory senses being most dominant, resulting in a distinctive cultural sensoryscape specific to Semarang. The findings identify four mechanisms through which multisensory experiences contribute to MTE: sensory immersion, cultural authenticity, emotional connection, and sensory memory formation. Notably, sensory immersion emerged as a novel dimension that complements the existing MTE framework. MTE was found to influence revisit intention via three psychological pathways: memory activation, emotional bonding, and social sharing. The study culminates in a multisensory experience design framework that can be adapted by other culinary destinations across Indonesia, emphasizing the significance of local cultural uniqueness.